The sequence of pulmonary vessels ligation during lobectomy for non-small cell lung cancer: A systematic review and meta-analysis - Huang, Kai-li; Deng, Han-Yu; Fan, Mingyu; Zheng, Qiangqiang; Lin, Shanyu; Zhu, Daxing; Zhou, Qinghua (European journal of surgical oncology, 2021)
The effects of ligating the pulmonary vein first or pulmonary artery first during lobectomy on the long-term survival of patients with non-small cell lung cancer (NSCLC) remain controversial. We conducted the first systematic review and meta-analysis to determine the association between different sequences of vessel ligation during lobectomy and the prognosis of patients with NSCLC. Literature retrieval was performed by systematically searching Embase, PubMed and Web of Science to identify relevant articles published from the inception of each database to November 2020. The overall survival (OS) and disease-free survival (DFS) of patients treated with vein-first ligation versus those treated with artery-first ligation during lobectomy were analyzed. A standard fixed-effect model test (Mantel-Haenszel method) was used to calculate pooled hazard ratios (HRs) and 95% confidence intervals (CIs). Heterogeneity was assessed using the Q-test and I2-test. Sensitivity analysis was performed to further examine the stability of pooled HRs. Five studies with a total of 1109 patients receiving lobectomy, including one randomized controlled trial and four retrospective studies, were included in this meta-analysis. The results showed that patients with vein-first ligation had a significantly better OS (HR 1.25, 95% CI 1.03–1.50; P = 0.02) and DFS (HR 1.54, 95% CI 1.16–2.04; P = 0.003) than those with artery-first ligation during lobectomy. Significant heterogeneity and publication bias were not observed during analysis. Our meta-analysis indicates that vein-first ligation may improve the prognosis of NSCLC patients receiving lobectomy. Therefore, vein-first ligation is recommended during lobectomy for patients with non-small cell lung cancer whenever possible.